Association Between Loneliness and Sleep-Related Problems Among Japanese Workers During the COVID-19 Pandemic - Tesen, Hirofumi; Konno, Yusuke; Tateishi, Seiichiro; Hino, Ayako; Tsuji, Mayumi; Ogami, Akira; Nagata, Masako; Muramatsu, Keiji; Yoshimura, Reiji; Fujino, Yoshihisa (Frontiers in Public Health, 2022)
Background: The coronavirus disease 2019 (COVID-19) pandemic has been linked to a rise in loneliness. Loneliness is associated with sleep-related problems, which in turn can be a risk factor for various psychiatric disorders. However, it is unclear whether loneliness is linked to sleep-related problems during the pandemic. Here, we studied the association between loneliness and sleep-related problems during the COVID-19 pandemic in Japan. Methods: A total of 33,302 individuals who indicated they were employed were surveyed online. The survey responses of 27,036 participants were analyzed. Odds ratios (ORs) were estimated using univariate and multiple logistic regression analyses. Results: Of those analyzed, 2,750 (10.2%) experienced feelings of loneliness. Further, sleep-related problems were significantly more common among those who felt lonely both in the short term (more than 3 days) and the long term (more than 3 months). The ORs was much weaker after adjusting for factors related to interpersonal connections, such as family and friendships, than after adjusting for factors related to socioeconomic status. Conclusion: Loneliness may be a risk factor for sleep-related problems in the COVID-19 pandemic. Having connections with family and friends may have a moderating effect on the occurrence of sleep-related problems. Keywords: loneliness, sleep, COVID-19